2017
DOI: 10.1371/journal.pone.0171380
|View full text |Cite
|
Sign up to set email alerts
|

The future of veterinary communication: Partnership or persuasion? A qualitative investigation of veterinary communication in the pursuit of client behaviour change

Abstract: Client behaviour change is at the heart of veterinary practice, where promoting animal health and welfare is often synonymous with engaging clients in animal management practices. In the medical realm, extensive research points to the link between practitioner communication and patient behavioural outcomes, suggesting that the veterinary industry could benefit from a deeper understanding of veterinarian communication and its effects on client motivation. Whilst extensive studies have quantified language compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
120
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(130 citation statements)
references
References 30 publications
2
120
2
6
Order By: Relevance
“…This may be related to what some have argued is a "do it yourself" attitude toward decision making (Jansen et al, 2010). Some have argued that it is incumbent on the veterinarian to adjust their approach to clients so that they are recognized as a potential advisor (Bard et al, 2017;Duval et al, 2017), and others have argued that it is also the responsibility of the farmer to recognize their veterinarian as a trusted advisor (Vaarst et al, 2003). Our study illustrates how both parties can work together to improve calf management.…”
Section: Strengthened Veterinarian Social Influence In Calf Managementmentioning
confidence: 59%
“…This may be related to what some have argued is a "do it yourself" attitude toward decision making (Jansen et al, 2010). Some have argued that it is incumbent on the veterinarian to adjust their approach to clients so that they are recognized as a potential advisor (Bard et al, 2017;Duval et al, 2017), and others have argued that it is also the responsibility of the farmer to recognize their veterinarian as a trusted advisor (Vaarst et al, 2003). Our study illustrates how both parties can work together to improve calf management.…”
Section: Strengthened Veterinarian Social Influence In Calf Managementmentioning
confidence: 59%
“…Lam et al [33] and Horseman et al [13,34] emphasise that veterinarians and other equine welfare professionals need to take advantage of current knowledge about human behaviour change to encourage owners to modify their behaviour to ensure the best welfare for their horse. Bard et al [35] found that veterinarians' communication with clients was mostly based on a directive style using the paternalism approach with the client having a passive role. However, Bard et al [35] found that this communication method was unlikely to encourage clients towards behavioural change and more likely to lead to psychological reactance.…”
Section: Discussionmentioning
confidence: 99%
“…Bard et al [35] found that veterinarians' communication with clients was mostly based on a directive style using the paternalism approach with the client having a passive role. However, Bard et al [35] found that this communication method was unlikely to encourage clients towards behavioural change and more likely to lead to psychological reactance. Lam et al [33] and Bard et al [35] suggested that veterinarians need to learn to communicate effectively with the client, by personalizing their response according to their client and building an emotional rapport with the client.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of assuming that we know and understand the constraints of the farmer, we can make an effort to ask open questions and really listen to farmers, actively trying to understand where they are coming from. In fact, current research suggests that the ‘typical’ veterinary approach to herd health management is underpinned by a lack of awareness of the farmer's goals and attitudes (Derks and others 2013, Bard and others 2017), so taking this small step could make a big difference. To improve communication, veterinarians would be advised to spend time exploring farmer motivations, allowing them to encourage engagement with veterinary recommendations by aligning these recommendations with existing farm priorities, while building a better interpersonal relationship through a shared understanding of farmers' perspectives.…”
Section: What Tools Do Veterinarians Have Available?mentioning
confidence: 99%
“…Our ongoing research suggests that veterinarians and farmers alike would benefit from a more farmer-orientated approach to herd health management, such as deliberately eliciting farmer motivations and experience, as well as explicit use of empathy and emotional support (Bard and others 2017). Used appropriately, these processes can enhance veterinary-farmer engagement and potentially improve the uptake of advice on farm, advice pertaining directly to medicines use or to the many other aspects of herd health.…”
Section: What Tools Do Veterinarians Have Available?mentioning
confidence: 99%